Mobile peoples - permanent places : nomadic landscapes and stone architecture from the Hellenistic to early Islamic periods in north-eastern Jordan - Huigens, Harmen O., (Access archaeology., 2019)
This study explores the relationship between nomadic communities in the Black Desert of north-eastern Jordan (c. 300 BC and 900 AD) and the landscapes they inhabited and extensively modified. This book focuses on the architectural features created in the landscape some 2000 years ago which were used and revisited on multiple occasions.